Nobody does it better: Identity, ideology, and the future of James Bond. (5th April 2022) - Johnson, Tyler; Funnell, Lisa
Abstract: Objective: We explore the possibility that ideology structures attitudes toward casting choices swapping the race, gender, or sexual orientation of existing characters within popular entertainment franchises. Methods: We conduct an original survey to gauge reactions to potential swaps within the James Bond film franchise. Results: American conservatives are significantly less interested in future Bond films should the main character be played by a black man, a black woman, a white woman, or someone who is gay or a lesbian. This relationship does not hold should the role go to someone under 25 or American. Conclusion: Ideology structures attitudes toward the world of popular culture in addition to and in similar ways to the world of politics.